2009
DOI: 10.1007/s11085-008-9133-y
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation Behaviour of Model Cobalt-Rhenium Alloys During Short-Term Exposure to Laboratory Air at Elevated Temperature

Abstract: The alloys being used in high-temperature systems such as stationary gas turbines and aircraft engines are iron-, cobalt-and nickel-based superalloys, amongst which the latter is the most widely used for highest temperatures. However, the use of Ni-based alloys is limited to temperatures below 1,100°C. The experimental Co-Re-based alloys are promising for high-temperature applications for service temperatures beyond 1,200°C. The purpose of the present investigations, at this still early stage of the alloy deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…In this stage of alloy development, emphasis is placed on basic deformation mechanisms which can be observed using transmission electron microscopy (TEM) [26,30]. The preliminary alloy cannot be tested in air at very high temperatures because severe oxidation would result in a complete disintegration of the whole sample [31,32]. Inert gas miniature creep specimen testing of experimental Co-Re-Cr alloys is also attractive because small amounts of materials are sufficient to study the creep behavior.…”
Section: Creep Testing Of New Co-re-cr Alloysmentioning
confidence: 99%
“…In this stage of alloy development, emphasis is placed on basic deformation mechanisms which can be observed using transmission electron microscopy (TEM) [26,30]. The preliminary alloy cannot be tested in air at very high temperatures because severe oxidation would result in a complete disintegration of the whole sample [31,32]. Inert gas miniature creep specimen testing of experimental Co-Re-Cr alloys is also attractive because small amounts of materials are sufficient to study the creep behavior.…”
Section: Creep Testing Of New Co-re-cr Alloysmentioning
confidence: 99%
“…It was shown in the previous study [1] that the s-phase is preferentially attacked during high-temperature oxidation in air as compared to the metallic matrix. This is not surprising because the s-phase is rich in the highly reactive element Cr (see Fig.…”
Section: Carried Out a Variety Of Experiments On Fe-cr Alloys Inmentioning
confidence: 86%
“…The first investigations of this class of alloys showed rather poor oxidation resistance during exposure to laboratory air [1,2]. The aim of the study at this stage of the Co-Re alloy development is to derive options for an improvement of the oxidation resistance at very high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…As soon as the Cr 2 O 3 scale does not prevent the contact of oxygen from the atmosphere with the metal substrate, oxidation of other elements, such as cobalt and rhenium takes place. Earlier investigations [3][4][5] on Co-Re-based alloys have shown that mass loss occurs during exposure to laboratory air because of evaporation of Re-oxide(s). It should be mentioned that the loss of rhenium occurs mainly by the formation of the gaseous rhenium oxides of type Re 2 O 7 [3].…”
Section: Materials and Experimental Proceduresmentioning
confidence: 99%
“…Earlier investigations of Co-Re-Cr model alloys have shown rather poor oxidation resistance during exposure to laboratory air [3,4]. Therefore, an important aim of the Co-Re alloy development must be to derive options for an improvement of the oxidation resistance at very high temperatures.…”
Section: Introductionmentioning
confidence: 99%